Safety assessment of the substance chopped carbon fibres, from carbonised polyacrylonitrile, for use in food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; et al. (EFSA Journal, 2022)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of chopped carbon fibres, from carbonised polyacrylonitrile, as food contact material (FCM) substance No 1086, which is intended to be used as a filler for polyether ether ketone (PEEK) polymer at up to 40% w/w. The plastic is intended for repeated use in contact with all types of foods under all conditions of use. The chopped carbon fibres have a length of ■■■■■ and a diameter of ■■■■■, with no fragments lower than ■■■■■ in any dimension. They do not include a fraction of particles at the nanoscale and are fully embedded in the PEEK matrix, and therefore the fibres and any fragments are not expected to migrate. Based on the results of a battery of three genotoxicity tests, the Panel concluded that the substance does not raise a concern for genotoxicity. Therefore, the CEP Panel concluded that the substance chopped carbon fibres, from carbonised polyacrylonitrile, with a minimum carbon content of 95% (at sizes not at the nanoscale) does not raise a safety concern for the consumer if the substance is used as a filler at up to 40% w/w for PEEK plastic in contact with all food types and under all conditions of use.